Customer motivation towards Pasar Tani (FAMA) / Rosliana Azali - Azali, Rosliana (2009)
The purpose for this project paper is to determine the factors that most influence customers go to Pasar Tani, to analyze the relationship between factors influence customers to shop with customer motivation towards Pasar Tani, and to identify which market best job of offering what customers want to shop in terms of it price and quality by comparing of Pasar Tani, supermarket and wholesale market under FAMA programmes. In addition, there are several factors that influence customers become motivated to shop at Pasar Tani especially in Melaka. The some factors that most influence are location, price, variety, freshness and choices. However, the factors that have significant relationship with customer’s motivation are location, price, variety, quality, services and choices. For the comparisons between Pasar Tani, supermarket and wholesale market by it price and quality of offering, supermarket is more valuable offering that most fulfill customers need and want. The findings from the study found several strategies that should recommend to FAMA Melaka. The several strategies are; FAMA Melaka should improve promotion activities, added some outdoor activities, increase training program for seller’s to attract customers, and located Pasar Tani at the strategic location.